PKR modulates sterile systemic inflammation-triggered neuroinflammation and brain glucose metabolism disturbances - Cheng, Wai-Yin; Lee, Xin-Zin; Lai, Michael Siu-Lun; Ho, Yuen-Shan; Chang, Raymond Chuen-Chung (Frontiers in Immunology, 2025)
Sterile systemic inflammation may contribute to neuroinflammation and accelerate the progression of neurodegenerative diseases. The double-stranded RNA-dependent protein kinase (PKR) is a key signaling molecule that regulates immune responses by regulating macrophage activation, various inflammatory pathways, and inflammasome formation. This study aims to study the role of PKR in regulating sterile systemic inflammation-triggered neuroinflammation and cognitive dysfunctions. Here, the laparotomy mouse model was used to study neuroimmune responses triggered by sterile systemic inflammation. Our study revealed that genetic deletion of PKR in mice potently attenuated the laparotomy-induced peripheral and neural inflammation and cognitive deficits. Furthermore, intracerebroventricular injection of rAAV-DIO-PKR-K296R to inhibit PKR in cholinergic neurons of ChAT-IRES-Cre-eGFP mice rescued the laparotomy-induced changes in key metabolites of brain glucose metabolism, particularly the changes in phosphoenolpyruvate and succinate levels, and cognitive impairment in short-term and spatial working memory. Our results demonstrated the critical role of PKR in regulating neuroinflammation, brain glucose metabolism and cognitive dysfunctions in a peripheral inflammation model. PKR could be a novel pharmacological target for treating systemic inflammation-induced neuroinflammation and cognitive dysfunctions.